Feasibility of randomizing Danish citizens aged 65-79 years to high-dose quadrivalent influenza vaccine vs. standard-dose quadrivalent influenza vaccine in a pragmatic registry-based setting: rationale and design of the DANFLU-1 trial - Johansen, ND; Modin, D; Nealon, J; Landray, M (BioMed Central, 2022)
Background High-dose influenza vaccines provide better protection against influenza infection than standard-dose in persons aged 65 years and above; however, in most countries, high-dose vaccines are not widely implemented. Assessing the relative effectiveness of high-dose compared to standard-dose vaccines on hospitalizations and mortality would enable more robust public health and cost-effectiveness estimates. This study aims to investigate the feasibility of conducting a pragmatic randomized clinical trial in Denmark comparing high-dose to standard-dose vaccines utilizing existing vaccination infrastructure and the Danish nationwide health registries for data collection. Methods The DANFLU-1 trial (NCT05048589) is a pragmatic, open-label, active-controlled randomized trial randomizing Danish citizens aged 65–79 years to either high-dose quadrivalent influenza vaccine or standard-dose quadrivalent influenza vaccine. The study utilizes the infrastructure of a private vaccination provider (Danske Lægers Vaccinations Service) for recruitment, inclusion, randomization, and vaccination. All collection of baseline and follow-up data including safety monitoring is performed centrally by the Department of Cardiology at Herlev and Gentofte Hospital, Copenhagen, Denmark using the Danish nationwide health registries. The study aims to include 40,000 participants during the 2021/2022 influenza season. The primary endpoints address feasibility and include the number of participants enrolled, randomization balance, and representativeness compared to the Danish general population. Relative vaccine effectiveness will also be assessed, however, this feasibility study is not powered for clinical outcomes and may be affected by the COVID-19 pandemic. Discussion The DANFLU-1 study is investigating the feasibility of conducting a large-scale pragmatic clinical trial in Denmark utilizing existing infrastructure and the Danish nationwide registries. This will provide valuable insight, especially for potential future fully powered vaccine trials, but also for trials wishing to investigate other interventions. Trial registration Clinicaltrials.gov: NCT05048589, registered September 17, 2021.